KADAR TRIGLISERIDA, KOLESTEROL, DAN LEMAK ABDOMEN AYAM BROILER YANG DIBERI CAIRAN SAUERKRAUT DALAM AIR MINUM - I Dian Kinasih; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
This study aims to prove a liquid of sauerkraut in the drinking water of broilers can lower triglyceride content, cholesterol content, and abdominal fat chicken broiler. Twenty four broiler chickens aged 1 day an average of 25-35 g/ tail. Broiler chickens were randomly divided into 4 groups and repeated 6 times. Each group was given liquid of sauerkraut in drinking water with concentrations of 0, 0.5, 1.0, 1.5 ml/L for 35 days. The results of the study treatment sauerkraut liquid in drinking water concentration of 1.0 ml/L and 1.5 ml/L have a significant effect (P <0.05) on triglyceride content, cholesterol content, and abdominal fat of broiler chickens. Giving sauerkraut liquid on triglyceride content broiler concentration of 1.0 ml/L and 1.5 ml/L significantly (P <0.05) lower triglyceride content compared with broilers without liquid of sauerkraut. Giving liquid sauerkraut on cholesterol content of broiler concentration 1.0 ml/L and 1.5 ml/L significantly (P <0.05) lower cholesterol content compared with broilers without liquid of sauerkraut. Giving liquid of sauerkraut against abdominal fat of broilers concentration of 1.0 ml/L and 1.5 ml/ L significantly (P <0.05) lower cholesterol content compared with broilers without liquid of sauerkraut. It can be concluded that the drinking water in sauerkraut liquid for broiler chicken lower triglyceride content, cholesterol content, and abdominal fat of broiler chickens at a concentration of 1.0-1.5 ml/L respectively, still at 69.4% -79.2%, 32 , 9%, - 39.4%, and 44.7% -50.3%. The measure of sauerkraut liquid in drinking water for the purpose of reduction in triglyceride content, cholesterol content, and abdominal fat of broiler chicken meat can be used at a concentration of 1.0 to 1.5 ml/L. Keyword: broiler chicken meat, sauerkraut liquid, triglyceride content, cholesterol content, and abdominal fat.